Comparison of Continuous and Programmed Intermittent Bolus Infusion of 0.2% Ropivacaine after Ultrasound-Guided Continuous Interscalene Brachial Plexus Block in Arthroscopic Shoulder Surgery - Hye-Jin Kim; Ji-Hye Baek; Seyeon Park; Ji-Uk Yoon; Gyeong-Jo Byeon; Sang-Wook Shin (Pain Research and Management)
Background. Despite the clinical effectiveness of the programmed intermittent bolus (PIB) method for epidural analgesia, evidence for this method in continuous interscalene brachial plexus block (CIBPB) is unclear. This study aimed to investigate the pain relief effect after arthroscopic shoulder surgery according to the administration method by comparing the PIB and continuous infusion methods among the administration methods of local anesthetics. Methods. Sixty-four patients aged >19 years scheduled for elective arthroscopic shoulder surgery were enrolled and divided into two groups. Ultrasound-guided CIBPB was performed to control postoperative pain. The infusion pump was programmed so that 0.2% ropivacaine was continuously injected at 1.1 mL/h in group A, whereas in group B, 0.1 mL/h was continuously injected and 4 mL was periodically injected at 4 h intervals. In both groups, a further infusion of 4 mL of 0.2% ropivacaine was administered if the patient requested additional analgesia, and the lockout time was set at 30 min. Postoperative pain quality was assessed using a visual analog scale (VAS), and the incidence of patients requiring additional analgesics, motor blockade using a modified Bromage scale (MBS), and consumed doses of local anesthetic were assessed. Results. The VAS and incidence of rescue analgesics were performed when the patient could communicate voluntarily after admission to the post-anesthetic care unit, and at 24 and 48 h after surgery showed no significant difference between the two groups. The MBS at 24 h after surgery was significantly higher in group B (p = 0.038). In the comparison of consumed doses of local anesthetic, group B had a significantly higher bolus injection dose (p = 0.047) and frequency of bolus use in the 24 h after surgery (p = 0.034). Conclusion. The PIB method in CIBPB after arthroscopic shoulder surgery provided a similar analgesic effect, with a higher bolus injection dose of local anesthetic and increased motor blockade than the continuous infusion method.